Random Scattering and Alternating Projection Optimization for Active Phase Control of a Laser Beam Array - Jeremy Saucourt; Paul Armand; Vincent Kermene; Agnes Desfarges-Berthelemot; Alain Barthelemy (IEEE Photonics Journal, 2019)
A fraction of a laser beam array, whose unknown piston phase relationships must be set to prescribed values, is launched into a scattering media with random transmission. The resulting output speckle pattern is sampled by an array of photodiodes measuring the local light intensity. The data feed an innovative optimization process, which controls a phase modulator array. Few iterations of the optonumeric loop lead to efficient and fast phase locking on any desired piston phase distribution.